Longitudinal retrospective study on the effect of season on milk production and composition in Rio Grande do Sul, Brazil - Sicheski, Sirineu José; Haygert-Velho, Ione Maria Pereira; Piuco, Marcos André; Busanello, Marcos; Calgaro, Júlia Laize Bandeira; Almeida, Paulo Sérgio Gois; Conceição, Jardel Menegazzi da; Velho, João Pedro (Semina: Ciências Agrárias, 2020)
This longitudinal retrospective study evaluated production and composition of milk from dairy cows according to season on a rural property in Palmeira das Missões, Rio Grande do Sul, Brazil, between January 2009 and December 2016. Milk yield per hectare per month was the primary variable measured, along with chemical composition (total dry extract, defatted dry extract, fat, protein, and lactose), somatic cell count, and total bacterial count of milk. Production in summer (513.53 kg/ha/month) did not differ (p > 0.05) from that in fall (504.69 kg/ha/month) or spring (564.63 kg/ha/month), but production in winter (639.20 kg/ha/month) was significantly higher than in summer (p < 0.0057). The real price of milk did not differ (p > 0.05) among seasons. The total dry extract content differed (p < 0.0059) between seasons. However, the cooler fall and winter seasons favored the production of total solids. The defatted dry extract content was higher (p < 0.0001) in winter (8.65%), compared to the other seasons of the year. Fat content did not differ (p > 0.05) among seasons. Protein content differed (p < 0.0200) between summer (3.01%) and winter (3.16%), but both seasons did not differ (p > 0.05) from fall (3.13%) or spring (3.05%). Winter lactose levels (4.52%) were higher (p < 0.0011) than during other seasons. The somatic cell count did not differ (p > 0.05) among seasons, demonstrating that the evaluated herd possesses standard mammary gland health. The total bacterial count did not differ (p > 0.05) among the seasons, demonstrating that the hygiene of the facilities remains constant. As expected, the temperature and humidity index varied (p < 0.0001) with the seasons, and the deleterious effects were more pronounced in summer and spring, as they are the hottest seasons in humid subtropical environments. The results emphasize that the organized management of milk production reduces the variation in milk composition, making it easier to maintain a consistent high milk quality and also generating extra revenue.